The Effect of Project-Based Learning on Students’ Speaking Ability in English Education Programs - Cattleya Wahyu Pravitha; Evan Afri (ITScience (Information Technology and Science), 2026)
This study aims to explore the effect of Project-Based Learning on students’ speaking ability in English Education Programs. The research is motivated by the continuing difficulty experienced by EFL students in developing oral communication skills, particularly in terms of confidence, fluency, pronunciation, vocabulary use, and active classroom participation. This study employed a qualitative case study approach to understand how students experienced project-based speaking activities in a specific classroom context. The participants consisted of English Education students enrolled in a speaking course and one lecturer who facilitated the implementation of Project-Based Learning. Data were collected through semi-structured interviews, classroom observations, and documentation of students’ project outputs, reflective notes, and learning materials. The data were analyzed thematically to identify recurring patterns and meanings related to students’ speaking development. The findings revealed three major themes: increased speaking confidence through repeated oral practice, development of speaking ability through authentic and collaborative projects, and continuing linguistic and psychological challenges during project implementation. These findings indicate that Project-Based Learning supports speaking development not only by improving students’ oral performance but also by creating a more communicative, collaborative, and reflective learning environment. The study contributes to the understanding of speaking ability as a socially mediated competence shaped by interaction, peer support, lecturer facilitation, and meaningful language use. The findings imply that lecturers should design project-based speaking activities with clear stages, structured feedback, and equal opportunities for student participation. Further research is recommended to examine the long-term impact of Project-Based Learning across different EFL contexts.